Leadership Model of Female School Principals Perspective Interpretation of Qur'anic Leadership Verses - Nasirussunah, Muhammad; Dahliana, Yeti (Program Studi Manajemen Pendidikan Islam UIN Sunan Ampel Surabaya, 2026)
The role of women as school principals often clashes with the habits of society that consider the position of top leader only suitable for men. In fact, a complete understanding of religious teachings never limits this. This study uses a comprehensive literature review to dissect and examine various sources of writing related to the variety of women's leadership in the lens of the Qur'an. The results of the study show that the coveted female leadership style prioritizes the path of deliberation, intellect, and an approach to compassion, as exemplified by Ratu Balqis. The main condition of the position of leader in the Qur'an fully emphasizes self-ability, honesty, and courage to do justice, not at all on gender. In the field, female leaders have proven to be resilient in organizing school affairs neatly and creating a supportive learning atmosphere. In conclusion, the biggest obstacle to women's leadership does not come from religious prohibitions, but from outdated and rigid societal customs. The success of female school principals today is clear evidence that Islamic teachings really uphold the value of justice, while slowly collapsing the narrow views that have been limiting women's movement space in the realm of education.